2015
DOI: 10.3390/ijms16035990
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Pluripotent Neural Stem Cell from the Embryonic Bovine Brain

Abstract: We recently isolated stem cells derived from the brain of a bovine fetus, utilizing a particular mechanical separation method. After improving our experimental conditions, we obtained neural stem cells using an optimized culture medium system. The cells were expanded, established in continuous cell culture and used for immunofluorescence cytochemistry. RT-PCR showed that embryonic neural stem cells (NSCs) not only expresses the protein Sox2, Nestin but also Pax6, Musashi proteins and were differentiated into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, the applications are highly restricted due to various ethical concerns. Due to the challenges in neural stem cell extraction and the difficulty in mesenchymal stem cell (MSC) transdifferentiation, techniques for induced pluripotent stem cell (iPS) producing are developed via various reprogramming processes with specific transcription factors, such as Oct4, Sox2, Klf4, and c-Myc [127]. However, such therapy may face the challenges in safety concern for iPS induced teratomas [128], efficiency limitation in continuous stem cell delivery, and the invasive procedures in clinical practice to reach the central venous system.…”
Section: Neuroregenerative Therapymentioning
confidence: 99%
“…However, the applications are highly restricted due to various ethical concerns. Due to the challenges in neural stem cell extraction and the difficulty in mesenchymal stem cell (MSC) transdifferentiation, techniques for induced pluripotent stem cell (iPS) producing are developed via various reprogramming processes with specific transcription factors, such as Oct4, Sox2, Klf4, and c-Myc [127]. However, such therapy may face the challenges in safety concern for iPS induced teratomas [128], efficiency limitation in continuous stem cell delivery, and the invasive procedures in clinical practice to reach the central venous system.…”
Section: Neuroregenerative Therapymentioning
confidence: 99%
“…Nestin, NSE, and GFAP were traditional makers of NSCs, neuron cells, and glial neurons, respectively (Hartfuss et al., 2001; Isgrò et al., 2015; Shaik et al., 2019). Oct4 and SOX2, two intracellular transcription factors, were used as indicators of stem cells (Gao et al., 2015; Lugert et al., 2010). We isolated NSCs from fetal mice and found that Ssd can induce the G0/G1 phase arrest and inhibit the differentiation, and Ssd can increase the stemness potential and thermotolerance of NSCs.…”
Section: Introductionmentioning
confidence: 99%